1997
DOI: 10.1086/515465
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proximal Spinal Muscular Atrophy Carriers and Patients by Analysis of SMNT and SMNC Gene Copy Number

Abstract: The survival motor neuron (SMN) transcript is encoded by two genes, SMNT and SMNC. The autosomal recessive proximal spinal muscular atrophy that maps to 5q12 is caused by mutations in the SMNT gene. The SMNT gene can be distinguished from the SMNC gene by base-pair changes in exons 7 and 8. SMNT exon 7 is not detected in approximately 95% of SMA cases due to either deletion or sequence-conversion events. Small mutations in SMNT now have been identified in some of the remaining nondeletion patients. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
471
3
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 490 publications
(512 citation statements)
references
References 41 publications
27
471
3
4
Order By: Relevance
“…In their assay, SMN2 amplified somewhat better than SMN1. The precision and accuracy of the method of Feldkö tter et al 14 are similar to, or slightly lower than, those of our method ( 10,11 and data herein), which is a modification of the original method of McAndrew et al 9 All of these methods, 9 -11,14 in addition to that of Gé rard et al, 13 determine SMN1 and SMN2 copy numbers reliably. Gé rard et al 13 also demonstrated an efficiency bias in their primer-extension assay, slightly in favor of SMN2, even though they generated larger products from SMN2 (27 bp) than those from SMN1 (23 bp).…”
Section: Quantification Of Pcr Bias Between Smn1 and Smn2supporting
confidence: 73%
See 3 more Smart Citations
“…In their assay, SMN2 amplified somewhat better than SMN1. The precision and accuracy of the method of Feldkö tter et al 14 are similar to, or slightly lower than, those of our method ( 10,11 and data herein), which is a modification of the original method of McAndrew et al 9 All of these methods, 9 -11,14 in addition to that of Gé rard et al, 13 determine SMN1 and SMN2 copy numbers reliably. Gé rard et al 13 also demonstrated an efficiency bias in their primer-extension assay, slightly in favor of SMN2, even though they generated larger products from SMN2 (27 bp) than those from SMN1 (23 bp).…”
Section: Quantification Of Pcr Bias Between Smn1 and Smn2supporting
confidence: 73%
“…SMN1 gene dosage analysis was originally developed by McAndrew et al 9 and modified as a non-radioisotopic assay as described previously. 10 The assay has since been modified further, using 23 cycles of PCR and the ABI Prism 310 Genetic Analyzer (Applied Biosystems, Foster City, CA).…”
Section: Smn1 and Smn2 Copy Number Assay (Smn Gene Dosage Analysis)mentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, multiplex PCR on a target sequence, a genomic reference, and internal standards for both the target and the reference sequences has been used. [2][3][4] An internal standard for a target sequence should have the same primer-binding sites as the target sequence but have an internal insertion/deletion or a different probe-binding site to allow its differentiation from the target by size or probe specificity. The target and its internal standard are amplified in the same reaction tube, so that they have approximately equal amplification efficiency.…”
Section: A Methods To Compensate For Different Amplification Efficienciesmentioning
confidence: 99%